Potency of Mangosteen Pericarp as Source of Antioxidant in Tea to Enhance Immune System: A Review - Yunita Satya Pratiwi; Rahmawati Rahmawati; Yushinta Aristina Sanjaya (Future Science, 2022)
Mangosteen is one of the tropical fruits that is widely planted in Indonesia. This fruit has a pericarp that is rich in antioxidant compounds that would be beneficial to be fortified in foods. Application in food can be found in food products rich in fats and oils to avoid rancidity or in medicinal products that can boost the immune system. One of the medicinal products that can be fortified with antioxidants is tea. Therefore, this paper is aimed to review the characteristics of bioactive compounds in mangosteen, the potency of antioxidants to enhance the immune system, and the application of mangosteen pericarp simplicial in tea production. The review of those studies is expected to enlighten not only the characteristics of mangosteen pericarp but also its potential applications in food products. Moreover, it would increase zero-waste food production, hence supporting the sustainability aspect for the environment.